Wave power extraction by an axisymmetric oscillating-water-column converter supported by a coaxial tube-sector-shaped structure - Deng, Zhengzhi (2013)
An analytical theory is developed to study the effects of a coaxial tube-sector-shaped supporting structure on the conversion efficiency of a suspended, circular OWC converter. An eigen-function expansion method is employed in a cylindrical coordinate system to study wave interaction with an OWC converter in finite depth of water. Effects of the supporting structure, OWC dimensions, wave direction on energy conversion efficiency, and optimization of power-takeoff devices are discussed. Our results show that the coaxial tube-sector-shaped support with an opening in the range of π/2–5π/4 can significantly increase the conversion efficiency and widen the frequency range over which the conversion efficiency is high.